Lipid Production in Cultivable Filamentous Fungi Isolated from Antarctic Soils: A Comprehensive Study - Victor Gallardo; Jéssica Costa; Marcela Sepúlveda; Yasna Cayún; Christian Santander; Excequel Ponce; Juliana Bittencourt; César Arriagada; Javiera Soto; Romina Pedreschi; Vania Aparecida Vicente; Pablo Cornejo; et al. (Microorganisms)
Antarctic soil represents an important reservoir of filamentous fungi (FF) species with the ability to produce novel bioactive lipids. However, the lipid extraction method is still a bottleneck. The objective of the present work was to isolate and identify cultivable FF from Antarctic soils, to assess the most effective methods for fatty acid (FA) extraction, and to characterise the obtained lipids. A total of 18 fungal strains belonging to the Botrytis, Cladosporium, Cylindrobasidium, Mortierella, Penicillium, Pseudogymnoascus, and Talaromyces genera and the Melanommataceae family were isolated and identified. The Folch, Bligh and Dyer, and Lewis extraction methods were assessed, and methyl esters of FA (FAMEs) were obtained. The Lewis method was the best in recovering FAMEs from fungal biomass. A total of 17 FAs were identified, and their chemical compositions varied depending on fungal species and strain. Oleic, linoleic, stearic, and palmitic acids were predominant for all fungal strains in the three assessed methods. Among the analysed strains, Cylindrobasidium eucalypti, Penicillium miczynskii, P. virgatum, and Pseudogymnoascus pannorum produced high amounts of FA. This suggests that the soils of Antarctica Bay, as well as harbouring known oleaginous fungi, are also an important source of oleaginous filamentous fungi that remain poorly analysed.